2014
DOI: 10.1093/icb/icu077
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic Genetic Variation in Natural Populations: A Predictive Framework

Abstract: Understanding how populations respond to rapid environmental change is critical both for preserving biodiversity and for human health. An increasing number of studies have shown that genetic variation that has no discernable effect under common ecological conditions can become amplified under stressful or novel conditions, suggesting that environmental change per se can provide the raw materials for adaptation. Indeed, the release of such hidden, or "cryptic," genetic variants has been increasingly viewed as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 52 publications
3
67
0
Order By: Relevance
“…4, for cooling times exceeding 20 days, may be associated also with cryptic genetic variations 43, 44 , which manifest themselves only under stress conditions. Mild heat shock has been reported to induce polyphenism in larvae of the tobacco hornworm, Manduca sexta , by revealing hidden genetic variations due to stress 45 .…”
Section: Discussionmentioning
confidence: 99%
“…4, for cooling times exceeding 20 days, may be associated also with cryptic genetic variations 43, 44 , which manifest themselves only under stress conditions. Mild heat shock has been reported to induce polyphenism in larvae of the tobacco hornworm, Manduca sexta , by revealing hidden genetic variations due to stress 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Since the speed of evolution is in part dependent on the degree of genetic variation underlying phenotypic traits under selection, evolution may proceed more rapidly when novel plasticity is revealed 24, 88, 89 .…”
Section: Phenotypic Plasticity As a Facilitator Versus Constraint On mentioning
confidence: 99%
“…CGV has received quite some renewed interest over the past decade and it is suggested that CGV provides the raw material of evolution and adaptation under different environmental conditions [17]. Unlocking CGV can be achieved by altered gene-expression regulation, such as the transcriptional response to changing ambient conditions.…”
Section: Introductionmentioning
confidence: 99%